Error Grammar Using Present Continuous Tense in Podcast YouTube Video by Loukgalf Kanatip: English - Ambalegin; Angelina Sandjaja (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
The objective of this study was to find out the errors in using pesent continuous tense in podcast YouTube Video by Loukgalf Kanatip and Lukkade Metinee from Thailand. In this research, the researcher’s purpose is to know how many errors grammar in using Present Continuous Tense in the podcast video on YouTube by Loukgalf Kanatip and Lukkade Metinee from Thailand. The qualitative method was being used by the researchers in this research. The observational method and the non-participatory technique were used for collecting the data. Identification was employed as a method, and competency in comparing was used as a strategy while analyzing the data. The script of Loukgalf Kanatip's podcast with Lukkade Matinee was used as the data and was evaluated narratively. Present Continuous Tense theory discovered by (Hewings, 2013) was used as the main theory to analyze the data. As a result, this research confirmed that 56 verbs using the end of -ing in a total 11 data were identified as error grammar in using Present Continuous Tense. The most dominant data is that there is a loss of -ing verbs and auxiliary words in the conversation on YouTube by Loukgalf Kanatip with Lukkade Matinee.